The rise of the 'Netflix tax' and what it means for sustaining European audiovisual markets. Issue 4 (1st October 2020) - Kostovska, Ivana; Raats, Tim; Donders, Karen
Abstract : This article builds on comparative case study research of four EU countries which have imposed 'Netflix taxes' – France, Germany, Belgium (Flanders) and Italy. It examines to what extent the introduced investment obligations are actually future-proof as part of developing long term sustainable audiovisual policy toolkits. We argue that Netflix taxes are introduced in a path-dependent manner, by building on familiar policy instruments, previously applied to other audiovisual players. We identify differences between the imposed investment obligations in terms of the type of Netflix taxes and their scope and pinpoint the similarities. Our findings show that Netflix taxes are driven by an economic rationale, that is to increase the global competitiveness of domestic films and improve their performance on global VOD platforms and that policymakers aim to integrate players such as Netflix, into their cultural models, rather than going against them.